Thai Public Expectations and Perceptions Toward Understanding in Thai Government’s Entertainment Complex Business Bill, 2025 - Sawatdee, Tanawoot; Tangwannawit, Patthanan; Srisuphotnanaont, Suniphan; Tangkunanan, Juthamad; Khamlai, Patsaphon (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study aimed to study the relationship between public expectations and perceptions regarding their understanding of the Entertainment Business Bill. The findings are intended to serve as a guideline for fostering public understanding. This research employed quantitative research. The study population consisted of a sample of 400 Thai citizens aged 20 years and older. Data were analyzed using descriptive statistics and inferential statistics. The research results revealed that many respondents were male, currently studying or holding a bachelor’s degree, employed in the private sector, and had an average monthly income of 20,001-25,000 Thai baht. Most respondents were aware of the Entertainment Complex Bill and agreed that its enactment would benefit the country’s development. The relationship factors between the public’s education level and income influenced their expectations, perceptions, and attitudes. Furthermore, the hypothesis testing confirmed that positive expectations and perceptions had an impact on the public’s attitudes towards the Entertainment Complex Bill. This indicates that individuals with positive expectations and perceptions tend to have a favorable attitude towards this bill. Additionally, the public’s attitude significantly influenced their understanding at a level of 1.0883, implying that those with a positive attitude are more likely to develop a more detailed understanding of the Entertainment Complex Bill. There should be incorporate effective public education initiatives that clearly communicate its underlying principles and rationale. Enhancing public understanding in this manner is essential to fostering positive attitudes, which in turn can lead to greater acceptance of the Entertainment Complex Bill, 2025.